2021
DOI: 10.4103/abr.abr_143_20
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Single-Nucleotide Polymorphisms within microRNAs Binding Sites of Neuronal Genes Related to Multiple Sclerosis

Abstract: Background: Different genetic variants, including the single-nucleotide polymorphisms (SNPs) present in microRNA recognition elements (MREs) within 3'UTR of genes, can affect miRNA-mediated gene regulation and susceptibility to a variety of human diseases such as multiple sclerosis (MS), a disease of the central nervous system. Since the expression of many genes associated with MS is controlled by microRNAs (miRNAs), the aim of this study was to analyze SNPs within miRNA binding sites of some neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…hsa-mir-4484 [552], hsa-mir-4511 [553], STAT3 [554], KLF5 [555], SRF (Serum response factor) [556], GATA3 [557] and USF1 [558] have been implicated as a principal mediator of kidney diseases. Studies have reported that hsa-mir-190b [559], hsamir-4693-5p [560], hsa-mir-1470 [560], hsa-mir-1825 [561], STAT3 [562], SREBF2 [563] and SRF (Serum response factor) [564] are necessary for neurological diseases. hsa-mir-4693-5p [565] and STAT3 [432] expression have been identified in COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%
“…hsa-mir-4484 [552], hsa-mir-4511 [553], STAT3 [554], KLF5 [555], SRF (Serum response factor) [556], GATA3 [557] and USF1 [558] have been implicated as a principal mediator of kidney diseases. Studies have reported that hsa-mir-190b [559], hsamir-4693-5p [560], hsa-mir-1470 [560], hsa-mir-1825 [561], STAT3 [562], SREBF2 [563] and SRF (Serum response factor) [564] are necessary for neurological diseases. hsa-mir-4693-5p [565] and STAT3 [432] expression have been identified in COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Despite strong evidence of microRNA dysregulation in MS patient samples and model organisms, there is limited literature on the role of microRNA variation in MS [ 12 15 ]. In contrast, variants in microRNAs and their processing machinery have been implicated in complex conditions such as cardio-metabolic conditions, colorectal cancer, glaucoma, Alzheimer’s disease and Parkinson’s disease [ 16 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rs1713418 A > G SNP is located in the 3′UTR region of the TEP1 gene [ 26 ]. SNP in the 3′UTR alters the ability of miRNA to bind to the target gene, which affects gene regulation and increases the risk of MS [ 31 ].…”
Section: Introductionmentioning
confidence: 99%